2010
DOI: 10.1088/0957-4484/21/12/125706
|View full text |Cite
|
Sign up to set email alerts
|

Two-terminal nanoelectromechanical bistable switches based on molybdenum–sulfur–iodine molecular wire bundles

Abstract: We demonstrate the application of Mo(6)S(3)I(6) molecular wire bundles for electrically controllable two-terminal on-off switches. We investigate how changes in the contact electrode material and geometry influence the device characteristics, hysteretic switching behavior and device stability. We also determine the device operating parameters, particularly the Young's moduli (40-270 GPa), operating current densities (3.2 x 10(5)-7 x 10(6) A m(-2)) and force constants. Although qualitatively, the properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…SCACs, when isolated from their bulk crystal, have nanoscale diameters of ≈1 nm and have unique physical and chemical properties such as 1D quantum confinement effects . This has led to their application in composites, molecular connectors, transistors, sensors, and photovoltaic devices . Very recently, the semiconducting 1D materials Sb 2 S 3 and Sb 2 Se 3 have been reported to have excellent optoelectronic properties by effectively reducing exciton decay due to the absence of dangling bonds on the surface.…”
mentioning
confidence: 99%
“…SCACs, when isolated from their bulk crystal, have nanoscale diameters of ≈1 nm and have unique physical and chemical properties such as 1D quantum confinement effects . This has led to their application in composites, molecular connectors, transistors, sensors, and photovoltaic devices . Very recently, the semiconducting 1D materials Sb 2 S 3 and Sb 2 Se 3 have been reported to have excellent optoelectronic properties by effectively reducing exciton decay due to the absence of dangling bonds on the surface.…”
mentioning
confidence: 99%
“…LiMo 3 Se 3 has a negative charge on the chain surface due to ionic interactions between Li + ions and Mo 3 Se 3 − chains [17] Mo 6 S 3 I 6 and Mo 6 S 4.5 I 4.5 , on the other hand, undergo vdW interactions and thus dangling bonds exist on their chains, similar to the case in graphene and transition metal dichalcogenides(TMDC). Due to these structural features [11], they have unique physical and chemical properties, which leads to many useful applications such as transistor [12,18,19,20], sensor [21], composite [13] and solar cell [22,23]. In addition, new 1D bulk materials, Sb 2 S 3 [24] and Sb 2 Se 3 [25,26], have been reported to have excellent optoelectronic properties due to the absence of dangling bonds on their chain surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jang et al 8,20 demonstrated a vertical, three-terminal, carbon-nanotube-based electromechanical switch, in which multiwalled carbon nanotubes were catalytically grown and used as active elements. Similarly, free-standing germanium nanowires 21,22 and Mo 6 S 3 I 6 nanowires 23 were also used as switching elements. Although such microswitches provide many advantages compared with conventional semiconductor switches and are being studied in detail [24][25][26][27] , most of those fabrications are incompatible with typical microfabrication processes.…”
Section: Introductionmentioning
confidence: 99%